Pendekatan Circular Economy Dalam Pengelolaan Sampah Plastik di Karang Taruna Desa Baros, Kecamatan Baros, Kabupaten Serang - Shanti Darmastuti; Intan Putri Cahyani; Afrimadona Afrimadona; Syarif Ali (Indonesian Journal of Society Engagement, 2020)
Various environmental problems that have occurred lately are more or less caused by the problem of garbage and waste from various activities of living things, especially humans. Therefore, good waste management is one of the solutions to current environmental problems. One of the main problems faced by partners is plastic waste management. Based on a preliminary field study conducted by the team, it was found that until now there had been no waste management activities carried out by the residents of Baros Village, both plastic waste management related to waste banks and plastic waste sorting. In this regard, one of the innovative solutions for plastic waste management is to apply the circular economy principle by sorting plastic waste and then managing and developing it to create a circular economy, which is recycling plastic waste into a product of economic value, so that can help people's economic life. In this case, through a circular economy approach, karang taruna gets socialization of a circular economy as a foundation in managing plastic waste. The activity began with coordination with officials in Baros Village and the board of the Setia Youth Organization, pretest, counseling, and continued with a posttest. The implementation of outreach activities is carried out online and only involves the karang taruna administrators due to the COVID-19 pandemic condition. From the results of the activities carried out, members of the karang taruna understand the importance of managing plastic waste to make it a commodity with economic value. Abstrak Berbagai permasalahan lingkungan yang terjadi belakangan ini sedikit banyak disebabkan oleh masalah sampah dan limbah dari berbagai aktivitas makhluk hidup, khususnya manusia. Oleh karena itu, pengelolaan sampah yang baik merupakan salah satu solusi dari permasalahan lingkungan saat ini. Salah satu kendala utama yang dihadapi mitra adalah pengelolaan sampah plastik. Berdasarkan studi lapangan pendahuluan yang dilakukan oleh tim, diketahui hingga saat ini belum ada kegiatan pengelolaan sampah yang dilakukan oleh warga Desa Baros, baik pengelolaan sampah plastik terkait bank sampah maupun pemilahan sampah plastik. Berkaitan dengan hal tersebut, salah satu solusi inovatif dalam pengelolaan sampah plastik adalah dengan menerapkan prinsip ekonomi sirkular dengan memilah sampah plastik kemudian mengelola dan mengembangkannya untuk menciptakan ekonomi sirkular, yaitu mendaur ulang sampah plastik menjadi produk yang bernilai ekonomis, sehingga dapat membantu kehidupan ekonomi masyarakat. Dalam hal ini melalui pendekatan ekonomi sirkuler, karang taruna mendapatkan sosialisasi ekonomi sirkuler sebagai landasan dalam pengelolaan sampah plastik. Kegiatan diawali dengan koordinasi dengan aparat di Desa Baros dan pengurus Karang Taruna Setia, pre test, penyuluhan, dan dilanjutkan dengan post test. Pelaksanaan kegiatan penyuluhan dilakukan secara online dan hanya melibatkan pengurus karang taruna karena kondisi pandemi COVID-19. Dari hasil kegiatan yang dilakukan, anggota karang taruna memahami pentingnya pengelolaan sampah plastik untuk dijadikan komoditas yang bernilai ekonomis. Kata Kunci: ekonomi sirkular; sampah plastik; komoditas; karang taruna